THE CAUSES OF HUMAN SMUGGLING(INDONESIA-MALAYSIA) AND THE POLICIES TAKEN BY THE INDONESIAN GOVERNMENT TO OVERCOME IT - Liu, Tiara Zulyansari (Universitas Nasional, 2024)
This research aims to analyze the causes of Human Smuggling experienced by Indonesian workers in Malaysia. The basic point of this research is the assumption that Indonesia, as a country that quantitatively contributes a very large number of labor exports (TKI) to other countries, at the same time on the